Aposentados da Maringá Previdência: um olhar sobre a velhice - Damasceno, Tatiane Gonçalves (2016)
The phenomenon of population aging has attracted the attention of researchers and public agencies, especially with regard to the issue of retirement. So check how retirees understand the processes because they spend during aging, as well as the forms of interaction that establish and mechanisms that rely in order to best experience this phase of their lives, becomes too important, especially for Anthropology . Aiming to understand the changes brought about by aging in the lives of retirees of Maringá-PR, this dissertation is research object retirees of the City Autarchy responsible for granting and maintenance of pension municipal statutory civil servants, the Maringá Previdência. Through formal interviews, informal conversations and participant observation sought to understanding that retirees are aging.